The rise and fall of illicit drug trafficking in the Peruvian Upper Jungle: an analysis from a state-society relations perspective - Manrique, Hernán (2018)
This article studies the transformation of State-society relations in the Peruvian Upper Jungle through the analyses of the rise and fall of drug trafficking in the Upper Huallaga Valley and the consolidation of «alternative development» in the San Martin region. After a brief historical introduction to the origins of drug trafficking in the valley, this paper focuses on the state efforts to fight drug trafficking since the late 1970's until the current days, in which the «Miracle of San Martin» managed to consolidate. The article discusses the importance of the type of drug policies to be implemented and the context in which they are put in practice, it discusses the role of local actors, sub-national governments and the international cooperation to consolidate the «Miracle of San Martín».